Terms of Education of Cotton - Umarkulova Barchinoy Nematovna (Web of Journals Publishing, 2023)
During the growing season, cotton undergoes several stages of development that differ in quality, which also affects the nutritional process. There are developmental stages of cotton sprouting, combing, flowering, weeding and ripening. The results of a study of how fertilizers affect cotton yields and the development of cotton during the growing season suggest that plant life should be divided into six periods. Plants do not always need the same amount of nutrients, both quantitatively and qualitatively. This factor varies depending on the growth, development and overall season of the plant. In this sense, all field crops are divided into two groups: short and long feeding during the growing season. For example, cotton is a plant that can be eaten for a long time during the growing season. It absorbs nutrients from the soil from the time the seeds germinate until the end of the growing season. After the autumn frosts hit the cotton, its growth period ends.
Keywords: Cotton, growth period, nutrition, seed germination, weeding, flowering, germination and ripening periods, nutrient uptake, fertilizer efficiency, cotton stalks.